2000
DOI: 10.1046/j.1464-410x.2000.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Early observations of the effect of extracorporeal shockwave lithotripsy on blood pressure: a prospective randomized control clinical trial

Abstract: Objective To determine, in a randomized controlled clinical trial, the effect of extracorporeal shock wave lithotripsy (ESWL) on blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 24 publications
(32 reference statements)
0
20
0
1
Order By: Relevance
“…The prevalence of HBP among patients with nephrolithiasis varies from 19.4% to 71.7% (11,14,35). HBP is poorly studied in cystinuric patients.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of HBP among patients with nephrolithiasis varies from 19.4% to 71.7% (11,14,35). HBP is poorly studied in cystinuric patients.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a number of uncontrolled and/or retrospective early reports suggested that ESWL might cause hypertension [19][20][21]. On the other hand, these postulated deleterious effects have not been confirmed by others [22][23][24][25] and two recent independent randomized controlled trials in the USA [26] and in the UK [27] have shown that there is no detectable increase in the incidence of hypertension following ESWL. In our study, patients who had received ESWL did not have higher blood pressure than those who had not received it, so any difference in blood pressure between stone-formers and controls cannot be ascribed to ESWL treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[7,8] The pain is of varying degrees (mild, moderate and severe). [9,10] Post SWL pain ranges from 22.5% to 74%. [11,12] It can be assessed according to the visual analog scale (VAS) which is a patient self-report on a scale of 0-10.…”
Section: Introductionmentioning
confidence: 99%
“…[13] It is usually treated on outpatient basis by the administration of analgesics in the form of NSAID or narcotics, and only few patients require hospitalization. [9,14,15] Hypertension is another complication of SWL. [9] According to the WHO, hypertension is defined as having systolic blood pressure (BP) above 140 mmHg or diastolic BP above 90 mmHg.…”
Section: Introductionmentioning
confidence: 99%